Advanced aqueous proton batteries: working mechanism, key materials, challenges and prospects. Issue 6 (November 2022) - Yang, Jia-Lin; Cao, Jun-Ming; Zhao, Xin-Xin; Zhang, Kai-Yang; Zheng, Shuo-Hang; Gu, Zhen-Yi; Wu, Xing-Long
Highlights: The development and merits of aqueous proton batteries are discussed. Key materials in aqueous proton batteries are comprehensively presented in terms of mechanism and performance. Current challenges and prospects for the development of aqueous proton batteries are analyzed profoundly. Abstract: With the advantages of high safety and environmental friendliness, aqueous batteries have shown beneficial application scenarios in the field of large-scale energy storage. Compared to the conventional metal ions storage processes, non-metal carriers like protons are less concerned about due to the unconventional storage mechanism, which could be regarded as a promising green battery technology with high power density and adequate lifespan. Owing to the unique working mechanism and properties, aqueous proton batteries (APBs) can deliver excellent low-temperature electrochemical performance with cost effectiveness, further allowing full play to the best ability of aqueous storage technique. However, the issue on lack of advanced electrode materials still hinders the research progress on commercial applications of APBs. In this review, we present a comprehensive summary on the development of APBs, from the perspective of electrode materials, electrolytes, and current collectors, including cross-sectional host and corresponding design principles and energy storage mechanism. This review aims to clarify the status quo and emerging challenges for further development of APBs devices. Graphical abstract: Image, graphical abstract